2016
DOI: 10.1002/jsfa.7814
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of light quality and fertility on biomass, shoot pigmentation and xanthophyll cycle flux in Chinese kale

Abstract: The results obtained in the present study support previous data demonstrating the stimulation of nutritionally important shoot tissue pigment concentrations following exposure to sole source blue/red LEDs compared to traditional lighting. Xanthophyll cycle flux was impacted by LEDs and this may support the role of zeaxanthin in blue light perception in leafy specialty crops. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In this study, 150 μmol · m −2 · s −1 × 1/4NSC was conducive to chlorophyll accumulation, whereas the treatment of 450 μmol · m −2 · s −1 × 1/2NSC was unfavourable for chlorophyll accumulation (Table 3). However, higher chlorophyll content in Chinese kale was induced in the higher fertility treatment 30 . This might be due to that the chlorophyll contents were more affected by light intensity (p ≤ 0.01) than NSC (p ≤ 0.05) (Table 3).…”
Section: Discussionmentioning
confidence: 90%
“…In this study, 150 μmol · m −2 · s −1 × 1/4NSC was conducive to chlorophyll accumulation, whereas the treatment of 450 μmol · m −2 · s −1 × 1/2NSC was unfavourable for chlorophyll accumulation (Table 3). However, higher chlorophyll content in Chinese kale was induced in the higher fertility treatment 30 . This might be due to that the chlorophyll contents were more affected by light intensity (p ≤ 0.01) than NSC (p ≤ 0.05) (Table 3).…”
Section: Discussionmentioning
confidence: 90%
“…18 Kopsell et al demonstrated that interactions of light quality, comparing fluorescent/incandescent and LED lights, and fertility significantly increased Chinese kale shoot biomass and pigment concentrations. 15 Yan et al demonstrated similar results comparing fluorescent/incandescent and LED lights with biomass accumulation but also discovered significant differences in vitamin C and soluble protein content in lettuce (Lactuca sativa). 19 Limited research exists on how different LED light ratios affect the mineral nutrient concentrations and accumulation.…”
Section: Discussionmentioning
confidence: 81%
“…Responses in kale biomass from the current study have been published previously. 15 Kale shoot fresh mass (FM) was influenced by light treatment, fertility treatment, and their interaction. Kale shoot tissue FM under ¼ strength fertility was 17.30, 9.24, 11.03, and 9.11 g per plant for the light quality treatments of fluorescent/incandescent light, 10% blue / 90% red, 20% blue / 80% red, and 40% blue / 60% red, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations